Co-designing technical innovations in the context of agricultural living landscapes - Triomphe, Bernard; Chimonyo, Vimbayi; Fuchs, Lisa; Rudiger, Udo; Vall, Eric; Mbaye, Banna; Sánchez Choy, José G.; Dubois, Mark (2023)
Codesign was a major focus of work package 1 that deals with the Transdisciplinary co-creation of innovations in Agroecological Living Landscapes (ALLs) in the target countries during 2023. This report provides an overview of progress achieved in 2023 with respect to codesign of technological innovations in 7 countries (Zimbabwe, Kenya, Tunisia, Burkina Faso, Senegal, Peru, Laos). It highlights the commonalities, contrasts and originalities among them in terms of actual approaches, existing practices, types of technologies selected for experimentation, experimental set-ups and monitoring and evaluation protocols. Hardly any experimental results per se are presented, as most countries did not yet have time to process them.